Discovering Self: Childbearing Adolescents' Maternal Identity. Issue 4 (July 2015) - Macintosh, Janelle; Callister, Lynn Clark
Abstract: Purpose: Adolescent pregnancy and motherhood have long been a topic of interest for many healthcare professionals. However, there are limited data on how childbearing adolescents incorporate motherhood identity into their sense of self. The purpose of this study was to explore how childbearing adolescents perceive motherhood as becoming part of their personal identity. Study Design: This qualitative study using ethnographic data collection involved 7 months of observation, interaction, and interviews. Methods: Data were collected from nine expectant adolescents during in-depth interviews. All participants were patients at a teen mother and child clinic staffed by certified nurse midwives and a pediatrician. Results: Narrative content analysis revealed the overall theme of discovering self, with three major themes: confirming the pregnancy, the loss of my body, and imagining my child in my arms. Clinical Implications: Adolescent mothers may need assistance to construct their maternal identity in order to strengthen self-perceptions and improve maternal/child outcomes. Abstract : This study explores how childbearing adolescents perceive motherhood as becoming part of their personal identity.